(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
The emergence of information and communication technology, globalization and transboundary criminal syndicates have changed the nomenclature of crimes committed globally. Transboundary crimes have remained one of the menaces that has continued to threatened global peace and security, hence, there is the need for a multilateral and multilevel approach to effectively curtail them. It is against this backdrop that the paper examines the legal framework to combat the crime of modern slavery and human trafficking in Nigeria, tracing the history of these ugly menace. Human trafficking is widely recognized as a form of contemporary slavery with a range of socioeconomic ramifications in Nigeria, Regrettably is a source, transit and destination country for human trafficking, which is a disgusting position to hold. The paper adopted a doctrinal method of data collection by relying on data from primary and secondary sources for analysis. The paper revealed among other things that, poverty, unemployment, weak laws and inadequate enforcement, systemic corruption, stigmatization, sophistication and financial war chest of cartels, influence of the social media, the traditional and cultural practices are the main drivers of human trafficking in Nigeria. The paper concluded by recommending that, there is urgent need by the government to address the social inequality, creation of more employment opportunities, carrying out awareness campaigns at all levels and the use of triangulated nexus of organ trafficking enforcement by countries among others..